Analisis Tingkat Pemahaman Mahasiswa Akuntansi Terhadap Konsep Dasar Akuntansi (Studi Pada Mahasiswa Program Studi Akuntansi Keuangan Publik Politeknik Negeri Bengkalis) - Molita Sarafina; Fachroh Fiddin (Politeknik Negeri Bengkalis, 2022)
One of the keys to mastering the science of accounting is to understand the basic concepts of accounting (Assets, Debts, Capital, Income and Expenses). If the basis of accounting has been mastered well, everyone will definitely easily live and practice it. One way for a person to understand the basics of accountants is by choosing accounting as an elective major in formal education starting from secondary education to higher education (Wardiningsih, 2020). The method used in this study is a quantitative descriptive method. The sample technique used is propotioned stratified random sampling, namely by first classifying according to its characteristics, namely based on the background of upper secondary education, namely the school of origin of the student (SMA IPA, SMA IPS, SMK AKUNTANSI). The data analysis used includes: Validity Test, Reliability Test, Normality Test, and Kruskall Wallis Test. The results of this study show that the level of understanding of the basic concepts of accounting regarding assets and capital between students who come from the high school of science, high school of social studies, and vocational school of accounting has differences. then the level of understanding of the basic concepts of accounting regarding debt, income, and expenses between students who come from the science high school, social studies high school, and accounting vocational school has no difference and can be said to have the same assessment. Kruskall Wallis Test Results the asset has a significance value of 0.012 0.05 and a capital variable of 0.003 0.05, These results show that H1 and H3 were received. furthermore, the results of the Kruskall Wallis Test of debt have a significance value of 0.114 0.05, income of 0.143 0.05 and expenses of 0.152 0.05. These results show that H2, H4 and H5 are rejected Keywords: Student Level of Understanding, Basic Concepts of Accounting, Assets, Debt, Capital, Income, and Expenses